Postcolonial Practice of Interfaith With-ness: Christian Expropriations from India - Baiju Markose (Indonesian Journal of Theology, 2020)
An attempt to develop the postcolonial practice of interfaith with-ness as a means of radical protest and resistance against the religious fundamentalism and crony capitalism in India has enormous significance today. The postcolonial practice of interfaith with-ness is not only a theoretical postulation but also a radical with-ness (being with) shared with the religious others. The idea proposes a radical politics of recognition, politics of difference, and politics of creative dialogue, rather than an apolitical “practice of tolerance” on which the traditional idea of interreligious dialogue is grounded. As a humble attempt, several Christian expropriations of the idea are being voiced in this essay with a spirit of religious confidentiality. And, the study uses empire criticism and intersectionality as the primary analytical tools.